Northwest history. Mining. Exploration. 1918-02-09 (1918)
Dreadnaught drifts for ore - would undercut mineral disclosed in surface operations - The Dreadnaught vein, in the Beaver creek district, Coeur d'Alene region, crops strongly for a distance of 400 feet, according to William J. J. Smith, manager. Ore containing a little galena can be walked upon, he says. Ore in a body a foot wide has been disclosed in a shaft sunk 12 feet on the vein. For the development of this vein an old intermediate tunnel is being extended. It has a depth of 65 feet and will attain a depth of 350 feet under the shaft in which ore was disclosed.